Leveraging the brand meanings in cross-cultural context : an exploratory study - Ho, Ivan (2008)
In expanding our understanding of brands and consumer behaviour, the interactions between brand associations, country-of-origin effects and cross-cultural influences were assessed. A theoretical framework adapted from past models was proposed. Findings indicated that youths engaged the use of functional and symbolic attributes in their choice of brands, subject to cultural influences.